Tape Recording of Side Scanning Sonar Signals - Hopkins, J. C. (The International Hydrographic Review, 2015)
A system for the tape recording of side scan sonar signals permitting automatic replay into a graphic recorder. The economical use of tape, and the facility to effect "online" monitoring of the tape recorded signals, are further advantages.